2018
DOI: 10.1111/mec.14801
|View full text |Cite
|
Sign up to set email alerts
|

Ecology can inform genetics: Disassortative mating contributes to MHC polymorphism in Leach’s storm‐petrels (Oceanodroma leucorhoa)

Abstract: Studies of MHC-based mate choice in wild populations often test hypotheses on species exhibiting female choice and male-male competition, which reflects the general prevalence of females as the choosy sex in natural systems. Here, we examined mutual mate-choice patterns in a small burrow-nesting seabird, the Leach's storm-petrel (Oceanodroma leucorhoa), using the major histocompatibility complex (MHC). The life history and ecology of this species are extreme: both partners work together to fledge a single chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 114 publications
(154 reference statements)
3
44
0
Order By: Relevance
“…Here, we provide evidence for sex-specific associations between MHC-II diversity and fitness in the early life of a monogamous species, thus calling for further research in species or populations with differing life-history strategies. A recent study in adult Leach's storm-petrels (Oceanodroma leucorhoa), a monogamous seabird, found a positive association between MHC diversity and reproductive success in adult females but not in males (Hoover et al, 2018). The underlying explanation was that males avoided females of low MHC diversity during mate choice but it was unclear whether reduced reproductive success of low MHC diversity in females also partly resulted from a direct, detrimental effect of reduced female quality on offspring viability.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we provide evidence for sex-specific associations between MHC-II diversity and fitness in the early life of a monogamous species, thus calling for further research in species or populations with differing life-history strategies. A recent study in adult Leach's storm-petrels (Oceanodroma leucorhoa), a monogamous seabird, found a positive association between MHC diversity and reproductive success in adult females but not in males (Hoover et al, 2018). The underlying explanation was that males avoided females of low MHC diversity during mate choice but it was unclear whether reduced reproductive success of low MHC diversity in females also partly resulted from a direct, detrimental effect of reduced female quality on offspring viability.…”
Section: Discussionmentioning
confidence: 99%
“…If there is such a link, taxa with relatively larger olfactory bulbs would be expected to be better at accurate mate choice for genetic compatibility prior to mating, possibly promoting long term genetic monogamy in such taxa (Colegrave, Kotiaho & Tomkins, 2002). For example, a recent study shows low levels of extra-pair paternity and male-mediated mate choice based on Major Histocompatibility Complex (MHC) loci in a largely monogamous seabird (Hoover et al, 2018). On the other hand, mating systems other than monogamy (e.g., polygyny in lek-breeding species) may also promote olfaction based mate choice.…”
Section: Survey Methodologymentioning
confidence: 99%
“…We captured Leach's storm-petrels (n = 10) at Bon Portage Island, Nova Scotia, 174 Canada (43°26' N, 65°45' W), where approximately 50,000 pairs breed annually (Oxley 175 1999). The age class (chick or adult) and burrow number of each individual were recorded 176 (Hoover, et al 2018). Approximately 75 µl of blood was taken from one male via brachial 177 venipuncture and stored in a microcentrifuge tube containing Queen's lysis buffer (Seutin, et 178 al.…”
Section: Sample Collection 173mentioning
confidence: 99%
“…It has been proposed that MHC genes can affect body odor by changing the peptide 576 Whittaker, et al 2016). In Leach's storm-petrels, males appear to select their mates based on 583 the MHC genotypes but females do not (Hoover, et al 2018). Some insects using odors to 584 select mates exhibit sexual dimorphism in the olfactory system (Brand, et al 2018).…”
Section: Or Genes Under Positive Selection 409mentioning
confidence: 99%